Agia varvara-Almyras : an Iron Age copper smelting site in Cyprus - Peege, Christina,; Della Casa, Philippe,; Fasnacht, Walter, (Archaeopress Publishing Ltd, 2018)
The Iron Age copper smelting site situated near the Cypriot village Agia Varvara is of particular importance among the ancient copper processing places in the Near East because it has revealed spatial as well as technological aspects of copper production in a hitherto rarely-seen depth of detail. This title presents the results of a comprehensive post-excavation analysis of the stratigraphy (part I), also of the geology, metallurgical materials (furnaces, tuyeres), finds (pottery, furnace lining, stone tools), as well as a synthesis of the copper smelting technology at Agia Varvara-Almyras (part II). The excavation analysis not only focuses on pyrotechnical information from individual furnaces, but also provides a detailed study of the spatial organisation as well as of the living conditions on the smelting site.